Penerapan Sociotechnical System pada Data Collection System - Tanoto, Dian Felita; Marcellinus, Yonathan; Hidajat, Monica (Bina Nusantara University, 2014)
Humans and technology are two things that can not be separated. The rate of population growth, which is growing rapidly, proportional to the needs of people in many ways. Each activity and human needs, should be documented, so any activity and human needs can be predicted. Therefore, the data need to be collected and stored properly, effectively, and accuratel. Socio-Technical System is expected to assist and facilitate human in performing the collection and storage of data. Socio-Technical System can be applied by taking into account various aspects ranging from social, psychological, computer science, and technical. Methods of Socio-Technical implementation consists of requirements analysis, system design, implementation, testing, deployment, maintenance. In the testing phase, it should be noted the social and psychological aspects of the user.